FEATURES OF THE IMMUNOLOGICAL PROFILE IN CHILDREN WITH JUVENILE ARTHRITIS OF SYSTEMIC ONSET DEPENDING ON DISEASE ACTIVITY (International Journal of Scientific Pediatrics, 2025)
Relevance. Systemic juvenile idiopathic arthritis (sJIA) is a distinct autoinflammatory subtype of juvenile arthritis, characterized by pronounced systemic inflammation and extra-articular manifestations such as fever, rash, and hepatosplenomegaly. The disease is associated with dysregulated production of proinflammatory cytokines (IL-1β, IL-6, IL-18), which determine its severity and increase the risk of complications. Conventional inflammatory markers, such as erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), are often insufficiently specific for accurate assessment of disease activity. Therefore, studying cytokine profiles and identifying reliable immunological biomarkers is particularly relevant for timely diagnosis, objective evaluation of disease activity, and optimization of individualized treatment strategies in children with sJIA, ultimately contributing to improved clinical outcomes and better prognosis. Objective. To study the characteristics of the course of juvenile arthritis depending on disease activity in patients with systemic-onset juvenile idiopathic arthritis (sJIA). Materials and Methods. A prospective cohort study including 74 children with juvenile arthritis (44 of them with sJIA) was conducted from 2021 to 2023. The diagnosis was established according to the International League of Associations for Rheumatology (ILAR) criteria (2001). Immunological assessments included measurement of proinflammatory cytokines (IL-1, IL-6, IL-18, TNF-α) using the RANDOX biochip technology, as well as autoimmune markers (S-100, serum ferritin) by enzyme-linked immunosorbent assay (ELISA) on a Multiskan FS, conducted in the clinical laboratory of RSSPMCP. The level of disease activity was assessed using the Juvenile Arthritis Disease Activity Score 27 (JADAS27). Statistical analysis was performed using StatPlus v8.0.3 and Microsoft Excel; correlations were assessed with Spearman’s rank correlation coefficient, and differences were considered statistically significant at p
Keywords: IL-18; systemic-onset juvenile idiopathic arthritis; IL-6; JADAS27